Building Traceability Between Functional Requirements and Component Architecture Elements in Embedded Software Using Structured Features - Yoo, Insun; Park, Hyoseung; Lee, Seok Won; Ryu, Ki Yeol (Applied Sciences (Switzerland), 2024)
In embedded software for critical domains such as medical devices and defense, requirement traceability is essential for ensuring quality attributes. Standards and regulations mandate traceability between requirements and artifacts such as design elements and code. However, existing methods often overlook the hardware-dependent nature of embedded systems or conduct traceability retroactively, which may affect consistency. This study introduces a structured feature-based approach to component architecture design, bridging the gap between requirements and design to ensure traceability. The structured feature model supports traceability between functional requirements, software components, and hardware elements in embedded systems. A case study demonstrates that structured features can effectively map the requirements to design artifacts, helping to visualize relationships through a traceability matrix. Although the process is manual, structured features improve efficiency in the early stages of design and create traceable links between requirements and architectural elements.
Keywords: Component architectures; Critical domain; Embedded-system; Functional components; Functional requirement; Medical Devices; Quality attributes; Requirements architectures; Requirements traceability; Structured feature; component architecture; embedded software; functional requirement; requirements traceability; structured feature